Requirements for an Online Automated Project Allocation System in Higher Education Institutions – A Case Study - Khurwolah, Mooneerah; Chuttur, Mohammad Yasser (Universitas Negeri Malang, 2020)
This paper presents the requirements gathered for an online automated project allocation system that can be used to assign final year projects to students registered in Higher Education Institutions (HEIs). The requirements are gathered for a well-known University in Mauritius. This research is motivated by several issues encountered with the current manual system in place at the studied institution and the need for adopting online systems following the COVID-19 outbreak. Following document analysis and a survey, important functional and non-functional requirements for an online automated project allocation system were uncovered. Gathered requirements also helped in determining a recommended workflow that can be adopted as best practice for final year project allocation. We posit that requirements presented in this paper can help develop a system that can be very useful and ultimately streamline the process for allocating projects typically important for Higher Education Institutions and other similar training institutions.